Transformation by T-antigen and other oncogenes delays Hsp25 accumulation in heat shocked NIH 3T3 fibroblasts - Gonin, Sandrine (Cell Stress Society International, 1997)
We have recently reported that transformation of murine NIH 3T3 cells by v-fos oncogene interfered with Hsp70 and Hsp25 accumulation after heat shock. Here, we have investigated the effect mediated by other oncogenes on the accumulation of these stress proteins. We report that T-antigen transformation of NIH 3T3 cells delayed and reduced the accumulation of Hsp25 after heat shock and decreased the heat-mediated phosphorylation of this protein. This decreased level of Hsp25 correlated with a reduced accumulation of the corresponding mRNA and was related to T-antigen level. In contrast, T-antigen had no effect on the expression of the major stress protein Hsp70 nor did it interfere with the level of Hsp90 or Hsp60. We report also that v-src or Ha-ras oncogenes delayed Hsp25 accumulation after heat shock but that only v-src reduced the heat-induced phosphorylation of this protein. v-src, but not Ha-ras, interfered with Hsp70 expression and none of these oncogenes had an effect on Hsp60 or Hsp90 levels. Taken together, these observations suggest that an altered accumulation of Hsp25 after heat shock is a common characteristic of NIH 3T3 fibroblasts transformed by different oncogenes.